Penggunaan Model Visual Interaktif dalam Meningkatkan Literasi Numerasi Siswa (Studi Kasus Siswa Kelas 1 Sekolah Dasar Negeri Sirnabaya II) - Novia Sundariani; Yani Suryani; Suharyanto H. Soro; Ida Tejawiani (Global Education Journal, 2026)
This research is motivated by the low numeracy skills of students aged 6–7 years. This study aims to describe the use of Interactive Visual Models in improving student numeracy. Researchers used a qualitative research paradigm with a case study approach. Data collection methods used observation, interviews, and documentation studies. The research sample consisted of 20 first-grade students (10 boys, 10 girls). The research instruments included numeracy tests (addition and subtraction operations 1–20 and image patterns), observations of teacher and student activities, and documentation. Qualitative data analysis was analyzed through a flow model (reduction, data presentation, conclusion drawing). The results showed an increase in average scores, student activity, interest, and involvement during learning also increased.